Composite electrochemical coatings of Ni-CrB2 from sulfuric acid and sulfamate electrolytes: formation, structure and properties - Polina Petukhova; Evdokiya Bushueva; Oksana Novgorodtseva (Chimica Techno Acta)
Electrodeposited coatings are in demand in many industries: due to the high adhesive strength to the base metal, they can be applied to complex-shaped products, and the thickness of the deposited coating can be controlled. However, standard electrolytic coatings do not always meet the necessary operating requirements. In this case, the formation of composite electrolytic coatings, which consist in the modification of electrolytes by various dispersed particles, becomes an urgent task. These particles are introduced into the electrolyte and deposited together with the precipitate metals, which leads to changes in the coating properties. In this article, the structure, adhesive and corrosion properties of nickel-chromium diboride composite coatings obtained in the electrodeposition process are studied. Precipitation was carried out in sulfuric acid and sulfamate electrolytes with a concentration of dispersed chromium diboride particles of 10-40 g/l. The coatings consist of nickel and CrB2 phases. The adhesive strength of the coating with a steel base is satisfactory; chipping and peeling were not observed. The corrosion resistance of sulfamate electrolyte coatings is higher than that of the coatings obtained from sulfuric acid electrolyte due to the compactness of nickel precipitates. Chromium diboride in the coating provides 1.5-2 times greater corrosion resistance.